(untitled) (Biological Sciences - PJSIR, 2001)
Internal membrane of bovine stomach is a by-product of slaughter house. Employing masked alum tannage on the delimed and well-bated membranes, they have been converted successfully into cream coloured novelty leather. The leather was found fit to fabricate ladies hand bags,jewellery boxes, wallets, purses etc. The stomach leather was light weight (168- 465 g) with adequate percent elongation at break (43.8 - 112. 3% longitudinally and 16 - 110% laterally) and has shrinkage temperature between 73 - 77°e. The tensile strength of the leather (100.6 N/cm2-423 Nzcm? longitudinally and 102.9 N/cm2-405 N/cm2Iaterally) was within the range of light weight fancy leathers. It bears good resistance to repeated flexing (20,000 flexes, dry). Its has moderate resistance to washing in solution of neutral detergents. Thickness of the leather (0.6 - 1.3 mrn) is also suitable for making the fancy leather products.